지속 가능한 에너지 시스템 구축을 위한 전기분해 수소 생산 플랜트 초기 건설비용 예측 - 강성욱(SUNGWOOK KANG); 김준헌(JOONHEON KIM); 박종화(JONGHWA PARK); 조대명(DAEMYEONG CHO) (한국수소 및 신에너지학회 논문집, 2024)
Hydrogen serves as a clean energy source with potential applications across various sectors including electricity, transportation, and industry. In terms of policy and economic support, governmental policy backing and economic incentives are poised to accelerate the commercialization and expansion of hydrogen energy technologies. Hydrogen energy is set to become a cornerstone for a sustainable future energy system. Additionally, when constructing hydrogen production plants, economic aspects must be considered. The essence of hydrogen production plants lies in the electrolysis of water, a process that separates water into hydrogen and oxygen using electrical energy. The initial capital expenditure (CAPEX) for hydrogen production plants can vary depending on the electrolysis technology employed. This study aims to provide a comprehensive understanding of hydrogen production technologies as well as to propose a method for predicting the CAPEX of hydrogen production plants.